The role of TGR5 as an onco-immunological biomarker in tumor staging and prognosis by encompassing the tumor microenvironment - Guan, Zhiyuan; Luo, Liying; Liu, Shengfu; Guan, Zhiqiang; Zhang, Qinggang; Wu, Zhong; Tao, Kun (Frontiers in Oncology, 2022)
The relationship between G protein–coupled bile acid receptor 1 (TGR5, GPBAR1) and, specifically, cancer has been studied in in vivo and in vitro experiments, but there is still a lack of pan-cancer analysis to understand the prognostic significance and functioning mechanism of TGR5 in different cancer-driving oncogenic processes. Here, we used Gene Expression Integration, Human Protein Atlas, and The Cancer Genome Atlas (TCGA) to perform a pan-cancer analysis of the role of TGR5 in all 33 tumors. In all TCGA tumors, the TGR5 gene expression has been assessed, and we found that the high TGR5 gene expression in most cancers is associated with poor prognosis of overall survival for cancers such as glioblastoma multiforme (p = 0.0048), kidney renal papillary cell carcinoma (p = 0.033), lower grade glioma (p = 0.0028), thymoma (p = 0.048), and uveal melanoma (p = 0.004), and then the lower expression of TGR5 was linked with poor prognosis in cervical squamous cell carcinoma and endocervical adenocarcinoma (p = 0.014), malignant mesothelioma (MESO) (p = 0.048), sarcoma (p = 0.018), and skin cutaneous melanoma (p = 0.0085). The TGR5 expression was linked with the immune infiltration level of the macrophage M2_TIDE and was also associated with DNA methylation in ovarian and breast cancers. The regulation of hormone secretion, Rap1 pathway, osteoclast differentiation, and bile acid pathway was involved in the functional mechanism of TGR5. Besides, gene expressions were different in different tumors detected by RT-PCR, and cell activity experiments have also found that TGR5 can increase the activity of renal cell carcinoma and reduce the activity of skin cancer and osteosarcoma cells. In this investigation, the aim was to assess the comprehensive overview of the oncogenic roles of TGR5 in all TCGA tumors using pan-analysis.